Responses to inpatient victimisation in mental health settings in England and Wales - Ellison, Louise (International review of victimology, 2019)
Mental health inpatients are known to be at risk of criminal victimisation, but the experiences of this vulnerable victim population seldom receive mention in the victimological literature. Against this backdrop, this article explores to what extent and in what ways mental health inpatients report victimisation, and provides the first systematic analysis of what the existing evidence base tells us about the subsequent responses of mental health services and criminal justice agencies, particularly in England and Wales. Identified knowledge gaps are problematised as impediments to evaluation of both policy and practice in this context. An agenda for future research is additionally sketched out.